Engaging Stakeholders: The Next Challenge in Corporate Environmental Reporting (Ökologisches Wirtschaften - Fachzeitschrift, 1995)
SustainAbility has recently embarked on the third phase of its work with the United Nations Envi-ronment Programme (UNEP). Our aim: to focus on >Stage 5< sustainable development reporting and stakeholders. Below, Andrea Spencer-Cooke, SustainAbility’s Programme Manager, reviews the progress to date.